Modeling and control of Cyber-Physical Systems subject to cyber attacks: A survey of recent advances and challenges - Mahmoud, Magdi S.; Hamdan, Mutaz M.; Baroudi, Uthman A. (Neurocomputing (Amsterdam), 2019)
•In general, the cyber-attacks in the literature can be classified into three main types: denial of service (DoS) attacks, deception attacks, and replay attacks. The focus of this paper will be on each of the aforementioned attacks such that the modeling and detection of each attack will be addressed, and the control of CPS under such attack will be discussed in details.•After a preliminary introduction of the subject, the paper is organized as follows. Detection of cyber-attacks are summarized in Section 2. In Section 3 the DoS attack is addressed. In Section 4, the results on the deception attack are given. Section 5 covers the replay attack.•Finally, challenges and future work are discussed in Section 6. Cyber Physical Systems (CPS) are almost everywhere; they can be accessed and controlled remotely. These features make them more vulnerable to cyber attacks. Since these systems provide critical services, having them under attack would have dangerous consequences. Unfortunately, cyber attacks may be detected, but after the damage is done. Therefore, developing a cyber system that can survive an attack is a challenge. In this paper, we are surveying the literature on security aspects of CPSs. First, we present some of existing methods for detecting cyber attacks. Second, we focus on three main cyber attacks, which are: Denial of service (DoS), deception, and replay attacks. In our discussion, we have surveyed some exiting models of these attacks, approaches of filtering CPS subject to these attacks, and approaches of control CPS subject to these attacks.